The potential role and limitations of echocardiography in acute respiratory distress syndrome. (April 2016) - Lazzeri, Chiara; Cianchi, Giovanni; Bonizzoli, Manuela; Batacchi, Stefano; Peris, Adriano; Gensini, Gian Franco
Bedside use of Doppler echocardiography is being featured as a promising, clinically useful tool in assessing the pulmonary circulation in patients with acute respiratory distress syndrome (ARDS). The present review is aimed at summarizing the available evidence obtained with echocardiography on right ventricle (RV) function and pulmonary circulation in ARDS and to highlight the potential of this technique in clinical practice (only articles in English language were considered). According to the available evidence on echocardiographic findings, the following conclusions can be drawn: (a) echocardiography (transthoracic and transesophageal) has a growing role in the management ARDS patients mainly because of the strict interactions between the lung (and ventilation) and the RV and pulmonary circulation; (b) there may be a continuum of alterations in RV size and function and pulmonary circulation which may end in the development of acute cor pulmonale, probably paralleling ARDS disease severity; and (c) the detection of acute cor pulmonale should prompt intensivists to tailor their ventilatory strategy to the individual patient depending on the echocardiography findings. Bearing in mind the clinical role and growing importance of echocardiography in ARDS and the available evidence on this topic, we present a flow chart including the parameters to be measured and the timing of echo exams in ARDS patients. Despite the important progress that echocardiography has gained in the evaluation of patients with ARDS, several open questions remain and echocardiography still appears to be underused in these patients. A more systematic use of echocardiography (mainly through shared protocols) in ARDS could help intensivists to tailor the optimal treatment in individual patients as well as highlighting the limits and potential of this methodology in patients with ALI.